Base-on Cloud Computing A new type of distributed application server system design - Hong Sun; Shi-ping Chen; Li-ping Xu; Ying-ying Chen (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
At this stage the application server systems, such as e-commerce platform , instant messaging system , enterprise information system and so on, will be led to lose connections , the data latency phenomena because of too much concurrent requests, application server architecture, system architecture, etc. In serious cases, the server is running blocked. The new type of application server system contains four parts: a client program, transfer servers, application servers and databases. Application server is the core of the system. Its performance determines the system’s performance. At the same time the application servers and transfer servers can be designed as the web service open to be used, and they can be achieved as distributed architecture by a number of hardware servers, which can effectively deal with high concurrent client application requests. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1578